Ukryć się w pugilaresie. Praktyki pisania Ignacego Domeyki - Mytych-Forajter, Beata (Śląskie Studia Polonistyczne, 2013)
The article by Beata Mytych-Forajter treats about works written by Mickiewicz’s friend, a geologist, and mining engineer who was very successful in Chile, South-America. Texts by Domeyko, located at the borderline of various forms and genres (a journal, diary, journey report), are, above all, connected with the need to note down oneself, leave an existential mark behind, and transform experiences into a notation. A strange author’s talentless writing who did not leave his portable wallet, serving the purpose of the shelter for thoughts, for the most of his life, but also a miniaturized ersatz of house is related to this identity project.